2008
DOI: 10.1111/j.1745-6584.2008.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Tracking Experiments in Match‐Index‐Refraction Porous Media

Abstract: A low-cost, noninvasive, three-dimensional (3D), particle tracking velocimetry system was designed and built to investigate particle movement in match-index-refraction porous media. Both a uniform load of the glass beads of the same diameter and a binary load of the glass beads of two diameters were used. The purpose of the experiments is to study the effect of the two loads on the trajectories, velocity distribution, and spreading of small physical particles. A total of 35 particles were released and tracked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…With PTV each seeding particle is traced and a Lagrangian flow field is obtained that contains less information about each point in the field as compared to PIV. As example of results with PTV Northrup et al (1993) found evidence of inter pore mixing within porous media at Re p < 1; PIV measurements in (Patil and Liburdy 2013) yield that at Re p ≈ 4 the spatial velocity variance increase when comparing the center plane data versus using data across the entire bed and Lachhab et al (2008) showed with PTV that velocity has a lognormal distribution in space for Re p < 1 and Stephenson and Stewart (1986) found that the latter velocity reaches its global maximum and minimum at distances near 0.2 and 0.5 D p from the wall for 5 < Re p < 250.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…With PTV each seeding particle is traced and a Lagrangian flow field is obtained that contains less information about each point in the field as compared to PIV. As example of results with PTV Northrup et al (1993) found evidence of inter pore mixing within porous media at Re p < 1; PIV measurements in (Patil and Liburdy 2013) yield that at Re p ≈ 4 the spatial velocity variance increase when comparing the center plane data versus using data across the entire bed and Lachhab et al (2008) showed with PTV that velocity has a lognormal distribution in space for Re p < 1 and Stephenson and Stewart (1986) found that the latter velocity reaches its global maximum and minimum at distances near 0.2 and 0.5 D p from the wall for 5 < Re p < 250.…”
Section: Introductionmentioning
confidence: 97%
“…However, optical techniques in porous media require all phases be transparent refractive index-matched (RIM) materials. This limits the range of materials that can be used but it still makes these techniques powerful for generic studies of the flow in porous beds with PTV (Johnston et al 1975;Stephenson and Stewart 1986;Saleh et al 1992;Northrup et al 1993;Peurrung et al 1995;Moroni et al 2001;Huang et al 2008;Lachhab et al 2008), PIV (Patil and Liburdy 2013) and Laser Doppler Anemometry (Yarlagadda and Yoganathan 1989). PIV require the flow to be seeded with a relatively large number of particles (Raffel 2007;Westerweel 1997).…”
Section: Introductionmentioning
confidence: 99%
“…So, contact erosion is usually initiated in a Forchheimer flow regime where both viscous and inertial forces must be considered. Measurements of flow characteristics at pore-scale have been realized by Nuclear Magnetic Resonance methods (Lebon, 1996;Johns, 2000) and by Laser Doppler Velocimetry (Giese, 1998) or Particle Tracking Velocimetry in a refraction-index matched porous medium (Rashidi, 1996;Lachhab, 2008;Huang, 2008). Numerical simulations have also been carried out by Lattice Boltzmann method (Maier, 1999) and by direct resolution of Navier-Stokes equations (Magnico, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The inner diameter of the tube is 50 mm, and all spheres have a diameter of 7 mm. Lachhab et al (2008) designed a PTV system and investigated particle motion in match-index-refraction porous media. One purpose with the experiments is to study the spreading of small particles.…”
Section: Introductionmentioning
confidence: 99%